A Systematic Literature Review For Smart Hydroponic System - Haifaa Jassim Muhasin; Ali Yahya Gheni; Nur Ilyana Ismarau Tajuddin; Nor Aziyatul Izni; Yusmadi Yah Jusoh; Khairi Azhar Azi (Institute of Advanced Engineering and Science (IAE), 2024)
Indexed by Scopus